You are on page 1of 6

Chapter 19 Definite Integrals 135

CHAPTER 19 0 (3 − 2 x ) −3 0

8. dx
= [ ]−3
−3 (3 − 2 x ) 4 ( −2)( −3)
bñÉêÅáëÉ=NV^=EéKONNF 1
= [(3 − 2 x ) −3 ]0−3
6
4 5x 4 4 1 1 1
∫0 5x dx = [ = ( −
1. 3 )
]0
4 6 27 729
5( 4) 4 13
= −0 =
4 2 187
= 320
4 4
∫1 ∫1 (2 x
1 3
9. (2 − x ) xdx = 2
− x 2 )dx
3
∫−1 ( x
1
2. 2
− 2 x + 4)dx = [ x 3 − x 2 + 4 x ]3−1 3 5
3 2x 2 x2
1 =[ 3
− ]4
5 1
= 12 + 5 2 2
3 3 5
1 4x 2 2x 2 4
= 17 =[ − ]1
3 3 5
32 64 4 2
= [ − ]−[ − ]
3 5 3 5
2 46
∫0 (4 x − 3 x 2 − 2 x )dx = [ x 4 − x 3 − x 2 ]20 =−
3
3.
15
= 16 − 8 − 4 − 0
=4
x2 + 2
2 2

2
10. ∫
1 x 2 1 ∫
dx = (1 + 2 x −2 )dx


1 3
4. ( x − 4 x + 3 x )dx = [ x 6 − x 4 + x 2 ]2−2
5 3 2
= [ x − ]12
−2 6 2 x
=0 2 2
= (2 − ) − (1 − )
2 1
=2
2 (3 x − 2 ) 3 2
5.
∫1 (3 x − 2)2 dx = [
9
]1

=
64 1

π
π sin(2 x + π4 ) π4
∫0 cos(2 x + )dx = [
4

9 9 11. ]0
4 2
=7
sin[2( π4 ) + π4 ] sin π4
= −
2 2
5
∫2 (1 − 2 x ) dx = [− 8 (1 − 2 x )
3 1 4 5 2 2
6. ]2 = −
4 4
1 =0
= − (9 4 − 34 )
8
= −810 π

∫0 sec
π
xdx = [tan x ]04
4 2
12.
3
(2 x + 1) 2 12 π
12
= tan − tan 0
7.
∫4 2 x + 1dx = [
2( 23 )
]4
=1
4
1 3
= [(2 x + 1) 2 ]124
3 π

∫−
1 x x π
dx = [2 sin ]−3 π
3
= (125 − 27) 13. π
cos
3 3 2 2 3
= 32
2 π π
= 2 sin + 2 sin
3 6 6
=2
136 Chapter 19 Definite Integrals

π π
− cos 3 x π4
∫0 ∫0 (a cos θ + b sin θ)dθ
2 2 2
sin 3 xdx = [ ∴
4
14. ]0
3
− cos 34π cos 0
π

= ∫ ( a sin 2 θ + b cos 2 θ)dθ


2
= + 0
3 3 π
2 1
∫0 (a cos θ + b sin θ)dθ
2 2 2
= + (b) 2
6 3 π
2+ 2 = ∫ ( a cos 2 θ + b sin 2 θ)dθ
2

= 0
6 π

+ ∫ ( a sin 2 θ + b cos 2 θ)dθ


2

0
0 0 π

∫− ∫
1
cos 2 xdx = (1 + cos 2 x )dx = ∫ ( a + b)dθ
2
15.
π
4 − π4 2 0
1 sin 2 x 0 ( a + b )π
= [x + ] π =
2 2 −4 2
π π
1 π sin 2 a+b
∫0 (a cos
1 sin 0
∴ θ + b sin 2 θ)dθ = π
2 2
= (0 + ) − (− − )
2 2 2 4 2 4
π+2
=
8
oÉîáëáçå=bñÉêÅáëÉ=NV=EéKONPF

π

∫ ∫0 (cos 2 x + sin 3x )dx = [ 2 sin 2 x − 3 cos 3x]0


8
6 1 1 π
16. π
2 sin 3 x cos xdx 1. 6

8


1 3 1
=2 (sin 4 x + sin 2 x )dx
8

π
= +
2 8 4 3
− cos 4 x cos 2 x 38π
=[ − ]π
4 2 8

− cos 23 π 3 π − cos π2 cos π4


π π

∫0 ∫0 (1 + 2 sin θ cos θ)dθ


cos 4
(sin θ + cos θ)2 dθ =
3 3
=( − )−( − ) 2.
4 2 4 2 π
2 2 = ∫ (1 + sin 2θ)dθ
3
= +
4 4 0
cos 2θ π3
=
2 = [θ − ]
2 2 0
π 3
= +
3 4

17. ∫0 sin 2 x sin 4 xdx
2π 1
= ∫ − (cos 6 x − cos 2 x )dx
π π

∫0 ∫0 ( 2 − 2 cos 2θ)dθ
7 1
(3 cos 2 θ + 4 sin 2 θ)dθ =
2 2

0 2 3.
− sin 6 x sin 2 x 2 π
=[ + ]0 7 1 π
= [ θ − sin 2θ]02
12 4 2 4
− sin 12 π sin 4 π − sin 0 sin 0 7π
=( + )−( + ) =
12 4 12 4 4
=0

π π π

∫0 [a(cos 2 θ − sin 2 θ) + b(sin 2 θ − cos 2 θ)]dθ


∫0 ∫0 2 (sin 4 x + sin 2 x )dx
1
2
sin 3 x cos xdx =
3 3
18. (a) 4.
π

= ∫ ( a − b) cos 2θdθ
2 1 1 π
= [ − cos 4 x − cos 2 x ]03
0 8 4
a−b π 9
= [sin 2θ]02 =
2 16
=0
Chapter 19 Definite Integrals 137

π
9 x 2 − 12 x + 4 + 2 x 3
∫0 sin
2 1 2
5. 3
θ cos 2 θdθ 10. (a) + = 3
x 3
(3 x − 2 ) 2
x (9 x 2 − 12 x + 4)
π
sin 2 2θ
∫ 2 x 3 + 9 x 2 − 12 x + 4
2
= sin θ dθ =
0 4 9 x 5 − 12 x 4 + 4 x 3
π


1 2 1
= − (cos 3θ − cos θ)sin 2θdθ 3 2x3 + 9 x 2 − 12 x + 4
4 0 2
π
(b) ∫2 9 x 5 − 12 x 4 + 4 x 3

1 2 1 1
=− [ (sin 5θ − sin θ) − (sin 3θ + sin θ)]dθ 3

1 2
8 0 2 2 = [ 3+ ]dx
π
2 x (3 x − 2 ) 2

1 2
=− (sin 5θ − sin 3θ − 2 sin θ)dθ −1 2
16 0 =[ 2 − ]32
1 − cos 5θ cos 3θ π
2x 3(3 x − 2)
=− [ + + 2 cos θ]02
16 5 3 71
=
2 504
=
15

π π

∫0 tan 2 xdx = ∫0 (sec x − 1)dx cos 3θ cos(2θ + θ)


4 4 2
6. =
11. (a)
π
cos θ cos θ
= [tan x − x ]04 cos 2θ cos θ − sin 2θ sin θ
=
π cos θ
= 1−
4 = cos 2θ − 2 sin 2 θ
= 2 cos 2θ − 1
π π

∫0 ∫0 (1 − 2 sin x cos x )dx


π
(sin x − cos x )2 dx = cos 3θ cos 3( 4 + φ)
2 2
7.
(b) =
π cos θ cos( π4 + φ)
= ∫ (1 − sin 2 x )dx
2

0 cos 34π cos 3φ − sin 34π sin 3φ


=
cos 2 x cos π4 cos φ − sin π4 sin φ
π
= [x + ]
2

2 0
π − 1 (cos 3φ + sin 3φ)
= −1 = 2
2 1 (cos φ − sin φ)
2
−(sin 3φ + cos 3φ)
8. No solution is provided for the H.K.C.E.E. =
question because of the copyright reasons. cos φ − sin φ
π
2 cos 2θ − 1 = 2 cos 2( + φ) − 1
b c 4
9. (a) = −(α + β) , = αβ π
a a = 2 cos( + 2 φ) − 1
β 2
∫α (ax + bx + c)dx
2
(b) = −2 sin 2φ − 1
= −(2 sin 2φ + 1)
1 1
= [ ax 3 + bx 2 + cx ]βα
3 2 −(sin 3φ + cos 3φ)
∴ = −(2 sin 2φ + 1)
1 1
= a(β − α 3 ) + b(β 2 − α 2 ) + c(β − α )
3 cos φ − sin φ
3 2 sin 3φ + cos 3φ
1 = 1 + 2 sin 2φ
= (β − α )[2 a(β + αβ + α 2 )
2 cos φ − sin φ
6
+ 3b(β + α ) + 6c] π π
sin 3φ + cos 3φ
∫0 dφ = ∫0 (1 + 2 sin 2φ)dφ
2 2
1 (c)
= a(β − α )[2(β 2 + αβ + α 2 ) cos φ − sin φ
6 π
− 3(β + α )2 + 6αβ] = [φ − cos 2φ]02
1 π
= a(β − α )( −β 2 + 2αβ − α 2 ) = +2
6 2
a
= − (β − α )3
6
138 Chapter 19 Definite Integrals

π sin 2 nx cos x − cos 2 nx sin x


∫0
12. (a) In = dx d n
(ii) x sin 2 x
sin x dx
π sin 2 nx cos x π
=∫ dx − ∫ cos 2 nxdx = x n (cos 2 x )(2) + nx n −1 sin 2 x
0 sin x
π sin 2 nx cos x
0
= 2 x n cos 2 x + nx n −1 sin 2 x
=∫
sin 2 nx π
dx − [ ]0 (b) From (a)(i),
0 sin x 2n
π sin(2 n + 1) x + sin(2 n − 1) x x n cos 2 x
=∫ dx − 0
0 2 sin x
1 π sin(2 n + 1) x ∫ ∫
= −2 x n sin 2 xdx + n x n −1 cos 2 xdx
= [∫
∫x
dx n
2 0 sin x sin 2 xdx
π sin(2 n − 1) x
+∫

dx ] 1 n n n −1
0 sin x =− x cos 2 x + x cos 2 xdx
2 2
1 π
= ( I n +1 + I n )
∫0 x
n
2 sin 2 xdx
∴ I n +1 = I n π
∫0 x
1 n
= − [ x n cos 2 x ]0π + n −1
cos 2 xdx
(b) From the result of (a), 2 2
In = In −1 = In − 2 = L = I2 = I1 1 n πn n
In = − ( π n ) + J n −1 = − + J n −1
π sin x 2 2 2 2
I1 = ∫0 sin x dx = π From (a)(ii),
∴ In = π x n sin 2 x

∫ ∫
= 2 x n cos 2 xdx + n x n −1 sin 2 xdx

∫x
1 n
∫0 (1 − x
1 31 cos 2 xdx
13. (a) 2
)dx = [ x − x ]0
3
∫x
1 n n n −1
2 = x sin 2 x − sin 2 xdx
= 2 2
3 π
∫0 x
n
cos 2 xdx
d
(b) x (1 − x 2 ) n π
∫0 x
1 n n
[ x sin 2 x ]0π − n −1
dx
= sin 2 xdx
= (1 − x 2 ) n + xn(1 − x 2 ) n −1 ( −2 x ) 2 2
= (1 − x 2 ) n − 2 nx 2 (1 − x 2 ) n −1
n
∴ J n = − In −1
2
= (1 − x 2 ) n + 2 n(1 − x 2 ) n − 2 n(1 − x 2 ) n −1
π
= (2 n + 1)(1 − x 2 ) n − 2 n(1 − x 2 ) n −1 ∫0 x cos 2 xdx = J3
3
(c)
(c) Integrating both sides of (b) from 0 to 1, 3
=− I2
[ x (1 − = (2 n + 1) In − 2 nIn −1
x 2 ) n ]10 2
(2 n + 1) In = 2 nIn −1 3 π2 2
= − (− + J1 )
2n 2 2 2
In = In −1
2n + 1 3π 2 3
= − J1
1 4 2
∫0 (1 − x
2 6
(d) ) dx = I6 3π 2 3 1
12 = − ( − I0 )
= I5 4 2 2
13 3π 2
3
12 10 8 6 4 = + I0
= ( )( )( )( )( ) I1 4 4
13 11 9 7 5 π
= 0.341 0 (corr. to 4 d.p.) As I0 = ∫0 sin 2 xdx
− cos 2 x π
d n =[ ]0
14. (a) (i) x cos 2 x 2
dx =0
= x n ( − sin 2 x )(2) + nx n −1 cos 2 x π 3π 2
= −2 x n sin 2 x + nx n −1 cos 2 x
∴ ∫0 x 3 cos 2 xdx =
4
Chapter 19 Definite Integrals 139

π
∫0 x cos 2 xdx
3
∫0 x − 3x + 2 dx
3
∴ 2

π
= ∫ x 3 (1 − 2 sin 2 x )dx
1 2
= ∫ ( x 2 − 3 x + 2)dx + ∫ −( x 2 − 3 x + 2)dx
0 0 1
π π
= ∫ x 3 dx − 2 ∫ x 3 sin 2 xdx
3
+ ∫ ( x − 3 x + 2)dx
2
0 0 2
x4 π π 1 3 1 3
=[ ]0 − 2 ∫0 x = [ x 3 − x 2 + 2 x ]10 − [ x 3 − x 2 + 2 x ]12
3
sin 2 xdx
4 3 2 3 2
1 3
π 3π 2 π 4 + [ x 3 − x 2 + 2 x ]32
∴ −2 ∫
0
x 3 sin 2 xdx =
4

4 11
3 2
π =
π2 2
∫ x sin xdx = ( π − 3) 6
3 2
0 8
3. x 2 + x − 2 = ( x + 2)( x − 1)
15. No solution is provided for the H.K.C.E.E.
question because of the copyright reasons. When x > 1 or x < −2 , x 2 + x − 2 > 0
When −2 < x < 1 , x 2 + x − 2 < 0

båêáÅÜãÉåí=NV=EéKONRF For −1 < x < 1 , x 2 + x − 2 = −( x 2 + x − 2)

1. (a) For any 0 ≤ x < π , sin x ≥ 0 For x > 1 , x 2 + x − 2 = x 2 + x − 2


∴ f ( x ) = sin x = sin x 3
∫−1 x + x − 2 dx
2

For any π ≤ x ≤ 2 π , sin x ≤ 0 1 3
= ∫ −( x 2 + x − 2)dx + ∫ ( x 2 + x − 2)dx
∴ f ( x ) = sin x = − sin x −1 1
x3 x2 x3 x2
0≤x<π = −[ + − 2 x ]1−1 + [ + − 2 x ]13
f ( x ) = 
sin x
3 2 3 2
− sin x π ≤ x ≤ 2π
2 26 8
A sketch of the graph is shown as follows. = −( − 4 ) + ( + − 4 )
3 3 2
y = 12

π
1 y = f (x) 4.
∫0 cos 2 x dx
π 3π
π
= ∫ cos 2 x dx + ∫ cos 2 x dx + ∫
4 4
x cos 2 x dx
O π 2π 0 π 3π
4 4
π 3π
π
= ∫0 cos 2 xdx − ∫ cos 2 xdx + ∫
4 4

π 3π
cos 2 xdx
4 4
sin 2 x π4 sin 2 x 34π sin 2 x π
2π =[ ]0 − [ ]π + [ ] 3π
(b) ∫0 sin x dx =2
2 2 4 2 4

π 2π
= ∫ f ( x )dx + ∫ f ( x )dx
0 π
π 2π `ä~ëëïçêâ=N=EéKONMF
= ∫ sin xdx + ∫ − sin xdx
0 π 3
∫2 4 x dx = [ x
3 4 3
= [ − cos x ]0π − [ − cos x ]2ππ 1. ]2
=4
= 34 − 2 4
= 65
2. Let y = x 2 − 3 x + 2 = ( x − 1)( x − 2)
4
∫1 (6 x + 3x )dx = [3 x 2 + x 3 ]14
2
When 0 ≤ x < 1 , y = x 2 − 3 x + 2 2.
When 1 ≤ x < 2 , y = −( x 2 − 3 x + 2) = [3( 4)2 + ( 4)3 ] − [3(1)2 + (1)3 ]
When 2 ≤ x < 3 , y = x − 3 x + 2 2 = 108
140 Chapter 19 Definite Integrals

`ä~ëëïçêâ=O=EéKONNF
4
∫1 (
1
1. x+ )dx
x
3
2x 2 1
=[ + 2 x 2 ]14
3
3 3
2( 4 ) 2 1 2(1) 2 1
=[ + 2( 4 ) 2 ] − [ + 2(1) 2 ]
3 3
2
=6
3

1 −1
∫0 ( x + 1)2 dx = [ x + 1]0
1 1
2.

−1 1
= +
1+1 0 +1
1
=
2

∫0 cos 2 dx = [2 sin 2 ]0
2 x x π
2
3.
π
= 2 sin − 2 sin 0
4
= 2

π π
∫0 ∫0 2 (1 − cos 2 x )dx
1
4. sin 2 xdx =
1 π 1 π
= ∫ dx − ∫ cos 2 xdx
2 0 2 0
x sin 2 x π
= [ ]0π −[ ]0
2 4
π 0 sin 2 π sin(2(0))
=[ − ]−[ − ]
2 2 4 4
π
=
2